Konfigurasi Sosial dan Kekuasaan Simbolik Guhanga dan Elite Politik Lokal di Bolaang Mongondow, Sulawesi Utara - , IRAWAN PAPUTUNGAN; , Prof. Dr. Sunyoto Usman ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The unfoldment of Bolaang Mongondow (Bolmong), although it has been framed in the same law construction as other regions in Indonesia, practically has different characteristics, especially in social and political configuration. Those dynamics occur on culture community (religious elites and Guhanga), politic community (political and bureaucratic elites), and civil society community. Each of those actors above in one side tries to present themselves as an authority of power, but in another side is exposed to competition fact. Another type of social relation later appears on more symbolic format. Briefly, the state power agenda principally will be developed by emphasizing the roles of decentralization, local wisdom, by means of custom and tradition roles. Since the basic mind of the legislative, judicial, and executive powers is later developed in local, then the roll of this symbolic power mind does not automatically form an unstable power distribution. The elite role is still more prominent than the role of culture community and civil society community. This thesis tries to draw the background of the forming of social configuration and Guhanga symbolic power and politic elite more deeply after the unfoldment along with the implication caused in the middle of increasingly contemporary local politic. The researcher incorporates a qualitative method with a descriptive approach. He views problems and understands their meaning associated with certain people in certain situation holistically but doesnât set social problems separately. Data collecting is conducted by observations, in-depth interviews and relevant document analysis of the object of the research. Based on the findings on the field, it can be stated that the political behavior of culture and politic community in social configuration does not only reinforce the structure of cultural existence, but also keep the reinforcement of politic obviously by creating power symbolically. The efforts of Guhanga and politic elite to legitimate the society tradition system are strengthened by their relation with other local elite, and also by their political strategy. When the culture representation has been strengthened, Guhanga has more power and influence in the society. Not only does this social configuration create significant cultural basic in Bolmong, but it also can be the symbolic power, even the interest collision with the local politic elite to get the structural power. In conclusion, the power spreads over in various social dimensions symbolically. This is resulted from the collective act of cultural and politic community who represents himself as Guhanga. Guhanga and politic elite are public. Everyone can be a Guhanga or politic elite who can influence social and politic configuration in the local.